Drug-induced tubulointerstitial nephritis in a retrospective study using spontaneous reporting system database - Oyama S; Hosohata K; Inada A; Niinomi I; Mori Y; Yamaguchi Y; Uchida M; Iwanaga K (Dove Medical Press, 2018)
Saki Oyama, Keiko Hosohata, Ayaka Inada, Iku Niinomi, Yasuhiro Mori, Yuki Yamaguchi, Mayako Uchida, Kazunori Iwanaga Education and Research Center for Clinical Pharmacy, Osaka University of Pharmaceutical Sciences, Takatsuki, Osaka, Japan Introduction: Tubulointerstitial nephritis (TIN) is a problem in clinical settings because drug therapy is the cause in most cases. Patients often present with nonspecific symptoms, which can lead to delays in the diagnosis and treatment of the disease. The purpose of this study was to clarify the rank-order of the association of TIN with the causative drugs using a spontaneous reporting system database. Materials and methods: Data were extracted from the Japanese Adverse Drug Event Report database of the Pharmaceuticals and Medical Devices Agency (Japan). Based on 5,195,890 reports of all adverse reactions, we obtained 3,088 reports of TIN caused by all drugs and calculated the reporting odds ratio (ROR) and 95% CI for TIN. Results: The 5 drugs with the highest RORs were gliclazide (ROR, 30.5; 95% CI, 17.4–53.2), tosufloxacin tosilate hydrate (ROR, 29.5; 95% CI, 21.3–41.0), piperacillin–tazobactam (ROR, 24.3; 95% CI, 19.4–30.5), cefteram pivoxil (ROR, 23.5; 95% CI, 12.5–44.2), and mefenamic acid (ROR, 22.5; 95% CI, 13.4–37.7). No sex-related difference was observed in drug-induced TIN. Most of the reports about TIN onset following the administration of culprit drugs were recorded within 12 weeks. Conclusion: Based on the results, a comprehensive study using a pharmacovigilance database enabled us to identify the dugs that most frequently induced TIN, so these drugs should be used carefully in clinical practice to avoid TIN. Keywords: tubulointerstitial nephritis, pharmacovigilance, spontaneous reporting system, reporting odds ratio, Japanese Adverse Drug Event Report database, JADER